Comparative Study of Morphometric Characteristics of Rohu and Jayanti Rohu under Captive Conditions in Tarai Region of Uttarakhand - Sharma, Lovedeep; Pant, Bonika; Tamta , Ekta; Ram, R. N. (International Journal of Livestock Research, 2018)
A comparative study of morphometric characteristics of rohu (Labeo rohita) and Jayanti rohu was conducted on the farmed fish specimen of College of Fisheries, Pantnagar, Uttarakhand. The descriptive statistical parameters and correlation coefficient (r) were analysed with independent variable (total length) and dependent variable (other morphometric parameters). The maximum correlation coefficient of average total length was obtained with fork length (0.977) and with standard length (0.979) in Jayanti rohu and rohu respectively. Minimum correlation coefficient, 0.356 in body depth-total length (BD-TL) and 0.424 in head length (HL -TL) was reported in rohu and Jayanti rohu respectively. Correlation coefficient in Jayanti rohu (BD-TL) is higher than rohu (0.778). The results reveal that morphometric parameters are significantly correlated to total length except caudal length in Jayanti rohu and body depth in rohu, respectively which signifies more body convexity of Jayanti rohu in comparison to rohu.